2017
DOI: 10.1016/j.cub.2017.07.062
|View full text |Cite
|
Sign up to set email alerts
|

A Neural Basis for Contagious Yawning

Abstract: Contagious yawning, in which yawning is triggered involuntarily when we observe another person yawn, is a common form of echophenomena-the automatic imitation of another's words (echolalia) or actions (echopraxia) [1]. The neural basis for echophenomena is unknown; however, it has been proposed that it is linked to disinhibition of the human mirror-neuron system [1-4] and hyper-excitability of cortical motor areas [1]. We investigated the neural basis for contagious yawning using transcranial magnetic stimulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 16 publications
0
9
0
1
Order By: Relevance
“…Sniffing, coughing, belching (Video 5A), and hiccup‐related sounds (Video 5B) were also documented in functional neurological disorders . Other physiological involuntary vocalizations are “contagious yawning” or groaning during sexual intercourse …”
Section: Methodsmentioning
confidence: 99%
“…Sniffing, coughing, belching (Video 5A), and hiccup‐related sounds (Video 5B) were also documented in functional neurological disorders . Other physiological involuntary vocalizations are “contagious yawning” or groaning during sexual intercourse …”
Section: Methodsmentioning
confidence: 99%
“…To investigate whether delivering rhythmic trains of mu-band (10 Hz) MNS to the right wrist had a significant effect on the occurrence of tics and the experience of the urge-to-tic in TS, we conducted a lengthy series of case studies in which 19 individuals with TS were video recorded while receiving randomly interleaved 1-min periods of MNS versus no stimulation. Throughout this period, participants were required to continuously report their self-estimated urge-to-tic by using a slider device reported previously [17]. Three patients withdrew from the study because they found the MNS uncomfortable, and a further three participants required a reduction in stimulation intensity (80% of threshold) to continue.…”
Section: Effect Of Rhythmic Mns On the Occurrence Of Tics And The Urge-to-tic In Tsmentioning
confidence: 99%
“…Contagious yawning is related to the social brain regions such as the STS and the mirror-neuron systems 29 . A recent study showed that the primary motor cortex is the important region for contagious yawning rather than the mirror-neuron systems 30 . Considering the developmental trajectory of yawning, spontaneous yawning is observed even in fetuses 11 .…”
Section: Discussionmentioning
confidence: 99%